2019
DOI: 10.33314/jnhrc.v16i41.1486
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Analgesic Efficacy of Ultrasound Guided Subcostal Transversus Abdominis Plane Block with Port Site Infiltration Following Laparoscopic Cholecystectomy

Abstract: Background: Patients have significant pain following laparoscopic cholecystectomy. Several modalities have been used to manage this pain. Subcostal transversus abdominis plane (TAP) block is one of the components of multimodal analgesia and has been described as an effective technique for postoperative pain management. This study compares the impact of subcostal TAP block with port site local infiltration following laparoscopic cholecystectomy for postoperative pain and opioid consumption.Methods: This is a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Baral et al 17 , in 2019 revealed the 24 hours' opioids consumption was significantly less (125 mg ± 25.42 versus 175 mg ± 25.42, p<0.001) in Subcostal TAP block group. This difference may be due to difference in study method and the type of blockade such as TAP, blind, subcostal or posterior method.…”
Section: Discussionmentioning
confidence: 91%
“…Baral et al 17 , in 2019 revealed the 24 hours' opioids consumption was significantly less (125 mg ± 25.42 versus 175 mg ± 25.42, p<0.001) in Subcostal TAP block group. This difference may be due to difference in study method and the type of blockade such as TAP, blind, subcostal or posterior method.…”
Section: Discussionmentioning
confidence: 91%
“…All included studies were of moderate or high quality based on JADAD Score ( Table 2 ). Out of 23 included studies, 14 studies ( 16 18 , 23 25 , 27 , 30 , 31 , 34 38 , 40 ) were conducted in Caucasian individuals, with the remaining nine studies ( 19 22 , 26 , 28 , 29 , 32 , 33 ) were conducted on an Asian population.…”
Section: Resultsmentioning
confidence: 99%
“…The subcostal approach to the TAP block has been documented to be effective for upper abdominal surgeries as it blocks the anterior cutaneous branches of the intercostal nerves (T7-T10). [ 8 ] Several studies have established the role of ultrasound-guided subcostal TAP block in providing better pain scores and diminishing morphine consumption in LC. [ 9 10 11 ] But to perform a UG subcostal TAP block requires an additional skill for anaesthesiologists and not all of them are trained in performing UG nerve blockade.…”
Section: Discussionmentioning
confidence: 99%
“…But we used paracetamol 6 th hourly as part of the multimodal regime. [ 8 ] Khan et al . compared the UG posterior TAP block with the subcostal approach with 63 patients in each group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation